Tembang Dolanan Jawa Sebagai Media Pemerolehan Bahasa Ibu Bagi Anak Usia Dini - Parosa, Jovita Ratu (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research was motivated by several cases of a child who did not understand the vocabulary of the first language, namely the mother tongue. With these problems, researchers searched for various relevant literature to find the right media to be used as a medium for learning mother tongue for early childhood, where at that age children experience rapid physical growth and cognitive development. In accordance with the purpose of this research, an effective media was found, namely Javanese dolanan songs. This media can be used for people who live in Java to deepen their knowledge of the mother tongue. This research will describe the use of Javanese dolanan songs as a medium of mother tongue acquisition for early childhood. This research method uses descriptive-qualitative method with data collection techniques using literature studies (literature study) whose results will be described in the form of descriptive narratives. From several literature studies such as scientific articles, books, and others, it was found that Javanese dolanan songs are very effective in early childhood.